2021
DOI: 10.1002/ab.21957
|View full text |Cite
|
Sign up to set email alerts
|

Sexism and its associated factors among adolescents in Europe: Lights4Violence baseline results

Abstract: Despite the efforts of recent decades to reduce gender inequality, sexism is still prevalent among adolescents. The objective of this study was to identify the main socioeconomic characteristics, personal experiences, resources, and competencies associated with sexism in a sample of adolescents from different European countries. Baseline data from the Lights4Violence project included 1555 students ages 12–17 from secondary schools in six European countries (Spain, Italy, Romania, United Kingdom, Portugal, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
(54 reference statements)
1
12
0
4
Order By: Relevance
“…Our results should be consumed with the results from other studies in mind-specifically those that explore the social context that may give rise to these gender disparities in online risk. While some extant research has identified protective population-level factors against online risks, such as a country’s level of Internet diffusion, it is also vital to recognize studies that demonstrate online gender disparities in risk also occur in settings where offline exposure to risk and violence is gendered as well [ 37 , 38 , 39 , 40 ]. Future research should continue to investigate how societal factors may influence gender differences in online exposure to harmful material.…”
Section: Discussionmentioning
confidence: 99%
“…Our results should be consumed with the results from other studies in mind-specifically those that explore the social context that may give rise to these gender disparities in online risk. While some extant research has identified protective population-level factors against online risks, such as a country’s level of Internet diffusion, it is also vital to recognize studies that demonstrate online gender disparities in risk also occur in settings where offline exposure to risk and violence is gendered as well [ 37 , 38 , 39 , 40 ]. Future research should continue to investigate how societal factors may influence gender differences in online exposure to harmful material.…”
Section: Discussionmentioning
confidence: 99%
“…We selected for the project those that were related with the promotion of positive intimate relationship or dating violence protective factors [ 34 ]. In this study, we selected covariates among our whole project variables that were also associated with sexism [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…El sexismo persiste como problema de salud pública de primer orden y confirma los resultados ya observados en adolescentes, tanto en el contexto espa ñol como en otros países europeos 6,15,17 . Los resultados muestran asociaciones entre tener buena relación con el entorno y menor sexismo, en línea con nuestra primera hipótesis, aunque no observamos asociaciones significativas entre el sexismo y el nivel educativo de las madres ni la experiencia en relaciones de pareja/sexuales.…”
Section: Discussionunclassified
“…El primero es identificar variables (individuales y del contexto inmediato) asociadas al sexismo en población adolescente. De acuerdo con la evidencia existente, nuestra primera hipótesis es que tener buenas relaciones con el entorno próximo (familia, compa ñeros/as, profesorado e instituto) y madres con alto nivel educativo se asocia a menor sexismo 15 . En cambio, haber tenido relaciones de pareja o sexuales se asocia a mayor sexismo 5,9 .…”
Section: Introductionunclassified